Study of The Impact of Beaching Coastal Area Mining on Social and Economic Aspects of The Community in Morotai Island District - Irfan Hi. Abd Rahman; Asri Jafar (International Journal of Education, Information Technology, and Others, 2020)
The research objective was to determine the impact of coastal mining on the social and economy of the community. Sampling and determining the measurement point in the field by means of stratified random sampling. This research was conducted in locations that are affected by coastal mining, namely the lands of the Momujiu Village and New Sabatai and Old Sabatai in Morotai Selatan District, Morotai Island Regency. From the search results in the field, it is estimated that there are around 13 land owners in the coastal area which have been used as sand mining land. Changes that occur at the economic level include changes in the livelihood system of people in coastal areas, which initially moved in the agricultural sector as the main sector of society, turning into non-agricultural communities such as sand mining workers. The social impact is a change in the interaction in the community between land owners and miners.